STUDY OF BOTTOM ASH UTILIZATION OF TIDORE RUM PLTU BALIBUNGA FOR CEMENT BRICKS MAKING: FAKULTAS TEKNIK UNIVERSITAS MUHAMMADIYAH MALUKU UTARA - Hi Ibrahim, Mohammad Marshus; Hermanto, Joni; Harminto, Sri Juniarti (DINTEK, 2025)
Fly Ash and Bottom Ash (FABA) are solid wastes from coal consumption in Steam Power Plants (PLTU). Approximately 55% - 85% of the ash produced from the coal consumption cycle is in the form of fly ash and the rest is in the form of bottom ash. This study was conducted to determine the characteristics of bottom ash waste that are right for cement bricks and how much the compressive strength value of cement brick tests using bottom ash waste is. This study is a quantitative analysis by conducting several tests to obtain descriptive purposes. Based on the results of the study, the use of bottom ash waste as an additional material for making cement bricks is considered to be able to reduce environmental impacts seen from the amount of bottom ash waste used during the cement brick study and from the results of the compressive strength test, the use of bottom ash waste variations of 50%, 75%, and 100% is not recommended for cement bricks.